Perception of Parents and Teachers in Education of Learners with Low Vision in an Inclusive Regular Public Primary School in Keiyo South Sub-County Kenya - Baraza, Beatrice; Omoke, Charles; Mwebi, Bernad (International Journal of Novel Research in Education and Learning, 2017)
The purpose of this study was to examine Perceptions of parents and teachers on the education of learners with low vision in an Inclusive regular public primary school in Keiyo South Sub-County, Kenya .The objectives of the study were to: establish the attitude of parents in the education of learners with Low Vision, find out the attitude of teachers in the education of learners with low vision, examine challenges facing parents in education of learners with low vision and determine challenges facing teachers in education of learners with low vision in an Inclusive regular public primary school in Keiyo South Sub-County. The study used a case study research design within a qualitative approach. The study was guided by Hoover Dempsey and Sandler theory. The target population was twenty-three (23) informants namely: 15 parents of learners with low vision, 6 teachers, 1head teacher and 1 quality Assurance standards officer. Saturated sampling technique was used to select 15 parents, 6 teachers, and 1 head teacher. Purposive sampling was used to select 1 quality assurance of standards officer. Interview schedules, questionnaires and focus group discussion guides were used as instruments for data collection. Trustworthiness and Authenticity of qualitative Instruments were ensured by use of multiple sources of data. Validity was established through expert vetting by two supervisors in the department of Special Needs Education and Early Childhood Development. Reliability issues were addressed by doing piloting in an inclusive regular public primary school in Eldoret. Qualitative data was analyzed thematically in an ongoing process as themes and sub-themes emerged in the study. The study findings revealed that both parents and teachers had positive attitude in educating the low vision learners. The challenges facing parents of children with low vision were: Lack of knowledge on handling learners/children with low vision, parents / women were stigmatized, poverty, ignorance and negligence from their spouses for having given birth to children who are visually impaired. The challenges facing teachers in teaching learners with low vision were: lack of teaching/ learning materials and equipment in implementing the daily living skills and in implementing core curriculum skills, poverty on the side of parents, absenteeism of children and lack of physical facilities in terms of adaptation in the physical environment that would accommodate low vision learners .The study concluded that though parents had a positive attitude to educate the low vision learners, poverty and stigmatization pull them back due to lack of knowledge on what core – curriculum and daily living skills entails. The study then recommends that parents need skills and knowledge on how to handle learners with low vision through seminars and workshops. Provide guidance and counseling to parents of these children with low vision and educate them just like their able - siblings. A study on mitigation measures against challenges that learners with low vision face would expound the present study
Keywords: Examine Perceptions; Regular Public Primary School; Low vision learners